THE PERCENTAGE OF CARCASS PARTS OF MEAL LOCAL DUCKS GIVEN BETEL LEAF SOLUTION INCLUDED IN RATIO - Sale, Maria; Handarini, Ristika; Dihansih, Elis (Universitas Djuanda Bogor, 2017)
This study was aimed at assessing the effects of inclusion of betel leaf extract solution in ration on the percentage of carcass parts of male local ducks. The study was conducted at the Poulty Farm of department of Animal Husbandry, Faculty of Agriculture, Djuanda University, Bogor from June to August 2016. Twenty-four male local ducks aged 2 weeks with average body weight of 450 g were used. The ducks were alocated into battery pens (150 cm x 40 cm) and fed BR-21E ration and betel leaf extract solution. Drinking water was given ad libitum. A completly randomized design with 4 treatments and 3 replicates was used. Treatments consisted of 100% comercial feed (R1) , comercial feed +2.5% piper betel solution (R2), commercial feed+5.0% piper betel solution (R3), and commercial feed + 7,5% piper betel solution (R4). Treatments were given at the second week following the adaption period. Data were subjected to an analysis of variance and a Duncan test. Result showed that the inclusion of betel leaf extract of 2.5, 5, 7.5% in the ration gave significant effects (P<0.05) on the percentage of carcass, wing, and tigh meat but not (P>0,05) on the percentage of back, breast and its parts, thigh, skin and femur. It was recommended that the inclusion of betel leaf extract in the ration be done by 5% in order to obtain high percentage of and more economical carcass, wing and thigh.Keywords : percentage of carcass part, male local duck, piper betle linn leaf solution